Peran Hamba Tuhan Dalam Mengajarkan Musik Gerejawi Bagi Remaja Pemuda Di GKSI Bethesda Sosok Kalimantan Barat - Candrawan Putra Daeli; Yeremia Hia (Jurnal Kabar Masyarakat, 2024)
Teaching church music for young people is one of the most important activities for God's servants to do. This music teaching aims to prepare young people to take part in the ministry, namely bringing music. Youth as the pillars of the church, must be properly equipped because they are the future of the church. Music is very important in worship. With music, it can encourage the congregation to praise and glorify the name of God. The introduction and teaching of ecclesiastical music for young people is one of the most important things for God's servants to do. Because with the magical music teaching program for young people, it can be a bridge for them to find their identity as servants of God and also to explore and hone the potential that exists within them. So that with the teaching of church music, it will make young people know and understand what church music is. They can also take part in the ministry of playing music at church services. Using music is a command from God as a means of praising and glorifying the name of God. The use of music in the Bible is not only used in praising and glorifying the name of God, but in the Old Testament it explains and gives written verses that musical instruments are also used when starting war (2 Kings 3:15), to celebrate victory in war (1 Samuel 10:5), to comfort hearts that are in a state of joy or sorrow, and also musk is used to expel demonic forces that disturb humans (1 Samuel 16:23). Meanwhile, in the New Testament, music is not only used to praise God, but music is also used to mourn people who have died (Matthew 9:23), and music is used to sing to God